Factors Related to Gastritis Events At The Ages 17-21 Years Old in The Work Area of Pesanggrahan Public Health Center (Puskesmas) in 2018 - Ida Setyaningsih (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Gastritis that occurs in developing countries is mostly experienced by young people with a predominant age of 20 years. The recurrence experienced can increase the risk of developing a disease that is more dangerous and difficult to cure, even causing death. This study was to determine the factors associated with the incidence of gastritis at the age of 17-21 years in the work area of ​​the Pesanggrahan Public Health Center in 2018. This study uses a quantitative type of research with a Case-Control study design. The population in this study were patients aged 17-21 years at the Pesanggrahan Public Health Center for the period June-August 2018. Cases were patients diagnosed with gastritis and controls were non-gastritis patients. Cases and controls were selected by accidental sampling technique as many as 50 people with a ratio of 1:1. Data were collected through interviews and analysis using the Chi-Square test with a value of = 0.05. The study showed that there was a relationship between several risk factors and the incidence of gastritis, including gender (OR=2,986, 95% CI = 2,680-3,654), knowledge (OR= 2,528, 95% CI=1,112-5,744), eating frequency (OR=9,333, 95% CI =1,121-77,704), Meal Time Interval (OR=5,670, 95%CI=2,144-14,997), Frequency of Drinking Tea (OR=2,923, 95% CI =1,245-6.865), Frequency of Spicy (OR=3.407, 95% CI =1.401-8.285), Frequency of Acid Eating (OR=1.196, 95% CI =1.801-2.478), Frequency of Instant Noodles (OR=10.444, 95% CI =2.855-38.211) while the risk factors which are not related to the incidence of gastritis are education, frequency of drinking coffee, frequency of drinking soda. It is necessary to improve health programs such as education, health promotion targeting teenagers in schools.